Enhancement of antioxidant activity and bioactive compound contents in yellow soybean by plant-extract-based products - Đurović, Sanja; Dragičević, Vesna; Waisi, Hadi; Pagnacco, Maja; Luković, Nevena; Knežević-Jugović, Zorica; Nikolić, Bogdan (Archives of Biological Sciences, 2019)
Abstract: Polyphenols present in different plant cell organelles increase the resistance of plants to various types of environmental stresses. We investigated the possibility of increasing the content of bioactive compounds in the seed of yellow soybean variety Laura. The soybean was treated during vegetation with five products based on plant extracts, on the assumption of enrichment of plants with various nutrients. Soybean flour extracts were screened spectrophotometrically for total phenolic content and antioxidant activity. The antioxidant activity was evaluated using three methods. The content of phenolic acids was determined by HPLC, and the raw protein content was estimated by the Kjeldahl method. Depending on the treatment, variations in the quantity of individual phenolic acids with up to 90% higher concentration as compared to the control were observed. Controlled usage of certain plant extracts can increase the concentration of the target group of bioactive compounds in the samples. The synergistic effect of proteins and phenolic compounds on the antioxidant activity of extracts was detected. The results of this study are not only important from the aspect of plant resistance to various types of stress, but also when considering soybean as a functional food. https://doi.org/10.2298/ABS190123024D Received: January 23, 2019; Revised: March 15, 2019; Accepted: April 8, 2019; Published online: April 9, 2019 How to cite this article: Đurović S, Dragičević V, Waisi H, Pagnacco M, Luković N, Knežević-Jugović Z, Nikolić B. Enhancement of antioxidant activity and bioactive compound contents in yellow soybean by plant-extract-based products. Arch Biol Sci. 2019;71(3):425-34.